Prognostic significance of resting cardiac power to left ventricular mass and E/e’ ratio in heart failure with preserved ejection fraction - Chen, Cong; Zhao, Jie; Xue, Ruicong; Liu, Xiao; Zhu, Wengen; Ye, Min (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiac power-to-left ventricular mass (power/mass) is an index reflecting muscular hydraulic pump capability of the heart, and E/e’ ratio is a specific indicator for identifying increased left ventricular filling pressure. Limited data exist regarding the prognostic value of incorporating power/mass and E/e’ ratio in heart failure with preserved ejection fraction (HFpEF). Methods: 475 HFpEF patients from the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist (TOPCAT) trial with complete baseline echocardiography data were included in our analysis. Patients were categorized into four groups according to power/mass and E/e’ ratio. The risk of outcomes was examined by Cox proportional hazards models and competing risk models. Results: Patients with low power/mass and high E/e’ were more likely to be males (60.5%), with higher waist circumference, and had a higher prevalence of diabetes (52.1%), atrial fibrillation (50.4%), and lower eGFR. Combined resting power/mass and E/e’ have graded correlations with LV dysfunction and clinical outcomes in patients with HFpEF. After multivariable adjustments, an integrative approach combining power/mass and E/e’ remained to be a powerful prognostic predictor, with the highest HRs of clinical outcomes observed in patients with low power/mass and high E/e’ (all-cause death: HR 3.45; 95%CI: 1.69-7.05; P = 0.001; hospitalization for heart failure: HR 3.27; 95%CI: 1.60-6.67; P = 0.001; primary endpoint: HR 3.07; 95%CI: 1.73-5.42; P < 0.001). Conclusions: In patients with HFpEF, an echo-derived integrated approach incorporating resting power/mass and E/e’ ratio remained to be a powerful prognosis predictor and may be useful to risk-stratify patients with this heterogeneous syndrome.